Transformative Power : Meeting the Challenge of Rural Electrification - Barnes, Douglas F. (World Bank, Washington, DC, 2014)
This brief is designed to illustrate in summary how a variety of countries have addressed the problems inherent in having successful rural electrification. By providing a snapshot of various programs and the many different ways in which these programs provide electricity to their rural populations, this note attempts to highlight best practices that should be emulated, and those factors that should be avoided.